Basic Facts about the United Nations 2014 - United Nations (United Nations, 2014)
This comprehensive handbook designed for the general public explains the structure of the United Nations, how the Organization works, the main issues it addresses and its importance for people everywhere. In addition to setting out the various roles played by principle UN organs and related organizations, Basic Facts about the United Nations documents the Organization’s contributions to international peace and security, economic and social development, human rights, humanitarian action, international law and decolonization. Appendices contain current data on UN membership and peacekeeping operations, as well as contact information for UN information centres, services and offices. This latest edition has been revised to take account of significant developments in the world and the Organization itself since 2011.